Implementation of Authoritative Parenting Patterns on Self-Confidence in Children Aged 4-6 Years in Rejoagung Village, Trangkil District, Pati Regency - Nawangsari, Meidina; Fakhruddin, Fakhruddin (International Journal of Education, Information Technology, and Others, 2025)
Parenting is a fundamental aspect in child development, affecting not only academic aspects, but also emotional and social aspects. In Rejoagung Village, this phenomenon is interesting to study, considering the unique social environment and cultural values ​​that play a role in the formation of parenting patterns. This study aims to explore the application of authoritative parenting patterns by parents in Rejoagung Village and its impact on the development of children's self-confidence. The research method used is qualitative with a case study approach, involving in-depth interviews and observations of parent-child interactions. Data collection techniques used through observation, interviews, and documentation. For data validity using triangulation techniques and source triangulation. Data analysis techniques with stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of authoritative parenting patterns in Rejoagung Village includes freedom for children to make choices in daily activities and clothing selection, accompanied by parental guidance. Consistent emotional support, opportunities for independence, and learning from experience and mistakes contribute significantly to the development of children's self-confidence. Children raised in this parenting style demonstrate good communication skills, high initiative, and strong adaptability in social situations.